MEMAHAMI PEMIKIRAN ABDULLOH SAEED TENTANG GERAKAN ISLAM PROGRESSIF DALAM KONTEKS SOSIOLOGI - fanani, zainuddin (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2019)
Abdullah Saeed is a prominent muslim, sultan of Oman, professor and director of the Center of Contemporary Islamic Studies at the University of Melbourne, Australia. The purpose of this study is to understand Abdullah Saeed's thoughts about progressive Islamic movements in the context of sociology. This study uses his book as primary source and other literature. The results showed that Abdullah Saeed could be accepted in a minority Islamic environment because his thoughts about the development of Alquran law that allows changes in accordance with the times. Understanding and interpreting Alquran according to the needs of today's society. Alquran, if comprehended holistically, contextually, and comprehensively will be able to answer problems in the modern era, because It is the perfect and final holy book. Alquran never stops being studied, both by Muslims and non-muslim Orientalists. They find messages in the text by searching the history and social conditions of the recipients of the text which includes culture, customs, beliefs, norms, values, as well as institutions of the recipients of Alquran. The last stage is connecting the text with the present context.